Perturbation of fluvial sediment fluxes following the 2008 Wenchuan earthquake. Issue 15 (23rd August 2017) - Wang, Wei; Godard, Vincent; Liu‐Zeng, Jing; Scherler, Dirk; Xu, Chong; Zhang, Jinyu; Xie, Kejia; Bellier, Olivier; Ansberque, Claire; de Sigoyer, Julia; ,
Abstract: Quantifying the removal of co‐seismic landslide material after a large‐magnitude earthquake is central to our understanding of geomorphic recovery from seismic events and the topographic evolution of tectonically active mountain ranges. In order to gain more insight into the fluvial erosion response to co‐seismic landslides, we focus on the sediment fluxes of rivers flowing through the rupture zone of the 2008 M w 7.9 Wenchuan earthquake in the Longmen Shan of the eastern Tibetan Plateau. Over the post‐seismic period of 2008–2013, we annually collected river sediment samples (0.25–1 mm) at 19 locations and measured the concentration of cosmogenic 10 Be in quartz. When compared with published pre‐earthquake data, the 10 Be concentrations declined dramatically after the earthquake at all sampling sites, but with significant spatial differences in the amplitude of this decrease, and were starting to increase toward pre‐earthquake level in several basins over the 5‐year survey. Our analysis shows that the amplitude of 10 Be decrease is controlled by the amount of landslides directly connected to the river network. Calculations based on 10 Be mixing budgets indicate that the sediment flux of the 0.25–1 mm size fraction increased up to sixfold following the Wenchuan earthquake. Our results also suggest that fluvial erosion became supply limited shortly after the earthquake, and predict that it could take a few years to several decades for fluvial sediment fluxes to go back to pre‐earthquake characteristics, depending on catchment properties. We also estimate that it will take at least decades and possibly up to thousands of years to remove the co‐seismic landslide materials from the catchments in the Longmen Shan. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : The evolution of detrital 10 Be concentrations of the frontal catchments in the Longmen Shan after the Wenchuan Earthquake is primarily controlled by the co‐seismic landslides areal extent. After the initial co‐seismic decrease, 10 Be concentrations are progressively increasing in several catchments over 5 years after the earthquake. We predict that the recovery time of the sediment flux after the Wenchuan earthquake vary from a few years to decades in the Longmen Shan.